Trends in education-economy-related inequalities in the prevalence of early childhood untreated caries in Guangdong, China from 2005 to 2021 - Linxin Jiang; Shaohong Huang; Linmei Wu; Yuandong Qin; Simin Li; Deborah Kreher; Daniel R. Reissmann; Gerhard Schmalz; Xiangyu Huang (BMC Oral Health)
Abstract Background Early childhood untreated caries (ECC) has numerous adverse effects on children and remains more prevalent in Asia than the global average. Despite recent improvements in ECC prediction and treatment, inequalities related to parental education and economic status may persist and have potentially worsened in the context of the COVID-19 pandemic. This study analyzed the trends and associated factors of education- and economy- related inequalities in ECC among 5-year-old children in Guangdong, China, from 2005 to 2021. Methods Data from three cross-sectional surveys from Guangdong, China, were utilized, including dental examinations of 2,584 five-year-old children and parental questionnaires. Logistic regression models and education-economy-related interactions were used to identify factors associated with ECC. The Slope Index of Inequality (SII) and Relative Index of Inequality (RII), derived from linear regression models, were applied to access trends in inequalities over the survey years. Results Children living in rural areas (OR = 1.97, 95%CI = 1.47 to 2.64) and those who have dental visits because of treatment (OR = 5.73, 95%CI = 2.73 to 12.05) were associated with a higher chance of having ECC, compared to their urban and non-visiting counterparts. Children whose parents had high (OR = 0.53, 95%CI = 0.31 to 0.88) or medium (OR = 0.64, 95%CI = 0.41 to 0.99) educational levels and those had high (OR = 0.60, 95%CI = 0.43 to 0.85) and medium (OR = 0.59, 95%CI = 0.42 to 0.84) economic levels were associated with a lower chance of having ECC compared those with levels. The highest education- and economy- related SII were observed in 2005. These declined by 14.0 and 4.3% points, respectively, in 2015, but increased again by 9.8 and 0.4% points in 2021. Besides, inequality as measured by SII increased continuously in rural areas. The RII values reflected similar trends in inequality distribution. Conclusions Children from rural areas, lower parental education and family economic level exhibited significantly higher ECC prevalence. The education- and economy- related inequalities persisted across different groups and demonstrated a downward trend overall, but inequalities have continued to rise in rural regions from 2005 to 2021.